Creative Selves / Creative Cultures Critical Autoethnography, Performance, and Pedagogy (Creativity, Education and the Arts, 2018)
This book addresses and demonstrates the importance of critical approaches to autoethnography, particularly the commitment that such approaches make to theorizing the personal and to creating work that embodies a social justice ethos. Arts-based and practice-led approaches to this work allow the explanatory power of critical theory to be linked with creative, aesthetically engaging, and personal examples of the ideas at work. By making use of personal stories, critical autoethnography also allows for commenting on, critiquing, and transforming damaging and unjust cultural beliefs and practices by questioning and problematizing the relationships of power that are bound up in these selves, cultures and practices. The essays in this volume provide readers with work that demonstrates how critical autoethnography offers researchers and scholars across multiple disciplines a method for creatively putting critical theory into action. The book will be vital reading for students, researchers and scholars working in the fields of education, communication studies, sociology and cultural anthropology, and the performing arts.